Greenhouse gases emissions and economic growth – evidence substantiating the presence of environmental Kuznets curve in the EU - Lapinskienė, Giedrė; Tvaronavičienė, Manuela; Vaitkus, Pranas (Technological and Economic Development of Economy, 2014)
The paper considers the relationship between greenhouse gas emissions (GHG) as the main variable of climate change and gross domestic product (GDP), using the environmental Kuznets curve (EKC) technique. At early stages of economic growth, EKC indicates the increase of pollution related to the growing use of resources. However, when a certain level of income per capita is reached, the trend reverses and at a higher stage of development, further economic growth leads to improvement of the environment. According to the researchers, this implies that the environmental impact indicator is an inverted U-shaped function of income per capita. In this paper, the cubic equation is used to empirically check the validity of the EKC relationship for European countries. The analysis is based on the survey of EU-27, Norway and Switzerland in the period of 1995–2010. The data is taken from the Eurostat database. To gain some insights into the environmental trends in each country, the article highlights the specific relationship in the country based on the level of its development. The similarities between individual countries are analysed in order to identify their basic common features.